2005
DOI: 10.1039/b509346e
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational circular dichroism of N-acetyl-l-cysteine protected gold nanoparticles

Abstract: Vibrational circular dichroism is used to determine the conformation of a thiol adsorbed on gold nanoparticles.Monolayer protected metal nanoparticles are of considerable interest due to their potential application in various fields such as bio-sensing, catalysis, electronics and nanotechnology.1 Whereas the physical properties of monolayer protected nanoparticles (MPNs) are largely associated with the metal core, their chemical behaviour such as solubility, molecular recognition and organization, is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 21 publications
2
81
1
Order By: Relevance
“…Vibrational CD spectroscopy was recently applied for the first time to AuNPs of about 2 nm core diameter in order to study the conformation of adsorbed chiral cysteine derivatives. [18,[48][49][50][51][52] Figure 3 shows IR and VCD spectra of AuNPs covered by the two enantiomers of N-isobutyryl cysteine (NIC). Whereas the IR spectra are identical for the two enantiomers, the VCD spectra show a mirror-image relationship.…”
Section: Purification and Size Separationmentioning
confidence: 99%
“…Vibrational CD spectroscopy was recently applied for the first time to AuNPs of about 2 nm core diameter in order to study the conformation of adsorbed chiral cysteine derivatives. [18,[48][49][50][51][52] Figure 3 shows IR and VCD spectra of AuNPs covered by the two enantiomers of N-isobutyryl cysteine (NIC). Whereas the IR spectra are identical for the two enantiomers, the VCD spectra show a mirror-image relationship.…”
Section: Purification and Size Separationmentioning
confidence: 99%
“…These results not only provided evidence for the existence of novel optically active nanomaterials, but also indicated that chiral effects are present in matter at the nanoscale. There have been published several additional reports confirming the observation of optically active nanoparticles using distinct chiral adsorbates as protecting ligands of Au, Ag, Pd nanoclusters, and semiconductor nanocrystals [5][6][7][8][9][10][11][12][13][14][15][16]. A chiral metallic cluster core model has been provided by recent measurements on the total structure determination of large and small gold-thiolate cluster compound [16][17][18][19].…”
mentioning
confidence: 90%
“…To probe the chiral nature of these particles, chiroptical techniques such as circular dichroism (CD) and vibrational circular dichroism (VCD) are particularly helpful. Based on the comparison between the experimental and calculated VCD spectra, the preferential conformation of N-acetyl-cysteine 10 and N-isobutyryl-cysteine 11 absorbed on gold particles was proposed. Theses results were in good agreement with those obtained from measurements on a SAM of the thiol on extended gold surfaces.…”
Section: Introductionmentioning
confidence: 99%